Estimating the proportion of patients infected with HIV who will die of comorbid diseases. - Braithwaite, R Scott; Justice, Amy C; Chang, Chung-Chou H; Fusco, Jennifer S; Raffanti, Stephen R; Wong, John B; Roberts, Mark S (The American journal of medicine, 2005)
Effective antiretroviral therapies have improved the prognosis for patients infected with the human immunodeficiency virus (HIV). We aimed to estimate the likelihood that HIV-infected patients would die of comorbid disease.
Keywords: Adult; Age Factors; Aged; Anti-Retroviral Agents; CD4 Lymphocyte Count; Comorbidity; Computer Simulation; HIV Infections; Humans; Middle Aged; Models, Statistical; Monte Carlo Method; Survival Rate; Treatment Refusal; United States; Viral Load